2015
DOI: 10.1136/sextrans-2015-052312
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of high-level azithromycin resistantNeisseria gonorrhoeaein England

Abstract: Epidemiological and microbiological investigations confirm that an outbreak of a gonococcal strain showing HL-AziR is ongoing in the North of England. Every effort should be made to identify and curtail dissemination of this strain as it presents a significant threat to the current recommended front-line dual therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 9 publications
1
84
0
1
Order By: Relevance
“…In our population azithromycin resistance has not been above 1.5% since 2012, which is lower than the overall European prevalence. Although both the mean MIC and the percentage of resistance have increased slightly during our study period, the high increase reported elsewhere in Europe, was not seen in our population [9,20]. The outbreak of azithromycin high-resistant isolates in England in 2015 occurred despite the use of dual therapy, as recommended by European and United States Centers for Disease Control and Prevention (CDC) guidelines [4,5].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In our population azithromycin resistance has not been above 1.5% since 2012, which is lower than the overall European prevalence. Although both the mean MIC and the percentage of resistance have increased slightly during our study period, the high increase reported elsewhere in Europe, was not seen in our population [9,20]. The outbreak of azithromycin high-resistant isolates in England in 2015 occurred despite the use of dual therapy, as recommended by European and United States Centers for Disease Control and Prevention (CDC) guidelines [4,5].…”
Section: Discussionmentioning
confidence: 63%
“…Taking the historical course of emerging antimicrobial-resistant gonorrhoea strains into account, without additional measures, a further decrease in ceftriaxone and azithromycin susceptibility is to be expected [1]. Moreover, high level azithromycin-resistant gonorrhoea has been reported in the United Kingdom (UK) since 2015 [9]. In addition, the first treatment failure on dual therapy of azithromycin and ceftriaxone was reported in 2016 [14].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the limited clonal spread as compared to ESC RS and quinolone resistance (Figure 1), as well as the inferred frequent return to susceptibility, implies that azithromycin resistance often incurs significant fitness costs. However, recent reports of an outbreak of azithromycin-resistant gonorrhea in England [27] and an increase in azithromycin resistance in the United States [8] raise concern that these fitness costs may be mitigated in some genomic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal mutations mediating low‐level resistance to beta‐lactams and tetracycline are common in N. gonorrhoeae isolates, and they are widespread across the phylogeny . While azithromycin resistance is less common than resistance to previously used drugs, resistance or reduced susceptibility has arisen across a large number of genomic backgrounds . In contrast, reduced susceptibility to ESCs (ESC‐RS) is primarily clonal, and the majority of ESC‐RS isolates belong to only a few major lineages .…”
Section: From Pathogen To Superbug: Treatment and Resistancementioning
confidence: 99%